The Role of Supply Chain Management Consumer Attitude as Intervening between Brand Images, Perceived Value and Revisiting Intention - Igus Rahmat Ginanjar; Ratih Hurriyati; Lili Adiwibowo; Vanessa Gaffar; Jumadil Saputra (International Journal of Supply Chain Management, 2019)
Abstract- The level of revisit intention in hotel resorts in Indonesia has increased from 2017 to 2018. From the data of the Indonesia tourism ministry, the last 10 months hotel occupancy rates in Indonesia have increased significantly compared to the year of 2017, but in the West Java region there is a phenomenon of fluctuation hotel room occupancy, especially in resort types, this is related to the rise and fall of brand image and perceived value. The arrangement of vacationer goal image has been looked into in the course of recent decades and is viewed as a standout amongst the most vital regions or research in image showcasing. It's important builds comprise of the image psychological and full of feeling image alongside its general image which has all the more as of late been incorporated and connected to the intellectual impacts of occasion decision and attitude. This study tests quantitatively whether attitude becomes intervening between brand image and perceived value towards revisiting intention, using a partial least square method to analyze data, a survey with questionnaires on 100 consumers of resort hotels in Bandung City by considering the supply chain management. The result showed that consumer attitude in Bandung City is not significant as an intervening role for brand image perceived value and revisit intention.